(untitled) (Journal of the College of Basic Education, 2022)
A search contains five chapters, the first one explained the concept of quality management and its importance, as it is in the education of modern trends, which faced a great demand and general attention to manage institutions by building a culture deeply about quality comprehensive sense that make responsibility of each individual to know it’s values ​​and principles in quality organization, in fact, decision making is a continuum of decisions that guide the activities to organize it all management levels. Head of Department is the Academic leader which has a great role in promoting morale members includes, reflecting good positive performance, as well as he’s contribution in identifying important positions to supply colleges and universities to fit with indicators vision, mission and goals of the university foundation. From this, it appears the importance of research to show the needs of the leadership role that is represented by department’s directors and physical activates units at the University of Al-Mustansiriya, and improve active decision-making to achieving the visions, goals and messages of their departments in line with the colleges and the university to which they belong. The research problem lies in the lack of knowledge of decision-making importance and how to make them according basis of facts represented in our research, which is supposed all directors of departments and units of physical activates in colleges Al-Mustansiriya University to be characterized by these decisions in accordance with standards and limitations of scientific bases for administrative to work successful. So researcher’s goal is to know the level of decision-making. The research areas: faculty members in the departments and units of physical activates at the University of Al-Mustansiriya, from 1/4/2012 until 1/9/2012, and spatial domain was in the colleges and university physical activates units at Al-Mustansiriya in Baghdad. In Part II contains the theoretical studies and similar and related to your search. Either Title III may methodology and past studies. Part 3 contains research procedures, the researcher used descriptive approach and style survey, on e sample of (54) teachers, which was chosen randomly, it was prepared by researcher to reach and achieve the goals of the research questionnaire decision. The fourth part showing analyzed and discussed results through statistical tables to determine the decision-making level of the sample surveyed. Finally Part V contains the following conclusions reached by the researcher in the study:1. The was a significant function in paragraphs Decision questionnaire to the department’s directors and of physical activates units at the University of AL-Mustansiriya the following items: (1, 2, 4, 5, 8, 12, 13, 16, 20, 21, 29, 30).2. The was no significant function in the paragraphs of the decision-making scale of department’s directors and of physical activates units at the University of AL-Mustansiriya the following items: (3, 6, 7, 9, 10, 11,14,15, 17, 18, 19, 22, 23, 24, 25, 26, 27, 28).3. There is a high level of research sample members in the decision making placed.The recommendations were as follows:1. Selecting people to occupy departments of physical activates and its units in universities who are eligible administrative leadership skills and experienced.2. Structured training for new director who selected to be manager of academic departments and others on administrative affairs, and leadership skills, and provide them with the knowledge and skill in all areas of their jobs.3. Establishment a culture of (co-decision) instead of making that decision alone, being a viable way to accept decisions and increase the effectiveness of the creative arts of leadership in total quality management.